Avaliação de novos biomarcadores no diagnóstico precoce da lesão renal aguda em pacientes com leishmaniose visceral em uso de Anfotericina B lipossomal - Bezerra, Gabriela Freire (2018)
The use of amphotericin B is very effective for treatment of visceral leishmaniasis (VL), but it is one of the main causes of acute kidney injury (AKI) in these patients. The liposomal formulation has less nephrotoxicity, but few studies with renal biomarkers have been done evaluating these effects in patients with VL. Aims: To study the association of the use of liposomal Anf-B with renal injury in patients with visceral leishmaniasis Methods: A prospective and longitudinal study was conducted between April 2015 and January 2018, and after exclusion criteria, 17 patients with VL were hospitalized in a reference hospital of infectious disease, Fortaleza, Ceará. The work was approved by the ethics committee CAAE: 61488016.8.3001.5044. The serum and urine were collected in two periods, first before patients started treatment (time 1) and the second at 72 hours to 168 hours after starting treatment with liposomal Anf-B (time 2). The renal parameters evaluated were: glomerular filtration rate (GFR) estimated by CKD-EPI, creatinine and serum urea, fractional excretion of sodium and potassium, proteinuria, albuminuria. Urinary biomarkers, MCP-1, KIM-1, VEGF and inflamatory biomarkers, IL-6, IFN-y were made by the enzyme-linked immunosorbent assay (ELISA) Results: Patients had a mean age of 43 ± 16 years and 12 (71%) were males. In the paired analysis, it was observed that during the treatment the patients did not have significant increases of creatinine and serum urea, as well as a decrease of the GFR. In addition, there was no difference between the fractional excretion of sodium and potassium and also between proteinuria and albuminuria. Regarding the biomarkers, urinary MCP-1 and KIM-1 showed significant increases during the use of liposomal Anf-B; (656.02 (413.81 - 929.55) vs 1871.92 (834.25 - 2299.33) pg / mg-Cr, p <0.05) and (1.62 (1.20-1.0, 97) vs. 2.51 (1.85-3.24) ng / mg-Cr, p <0.05), respectively. IL-6 levels decreased significantly during treatment (17,37 (8,74 – 49,08) vs 0,21 (0,00 – 3,55) pg/mL, p<0,05). The levels of VEGF and INF-y did not show significant differences. Besides that, urinary MCP-1 levels correlated statistically with the renal markers currently used in clinical practice. Conclusions: The use of liposomal Anf-B did not present significant nephrotoxicity according to the classic parameters of renal function evaluated, but may have contributed to renal injury evidenced by elevation of urinary MCP-1 and urinary KIM-1.